Social explanations for ethnic differences in education - Parameshwaran, M (2013)
This thesis investigates how variations in individual social contexts account for the existence of ethnic differences in educational outcomes. Four questions are answered. First, how are school ethnic and poverty compositions associated with ethnic differences in educational progress? Second, how are individual and school cohort level religious attitudes and behaviours associated with ethnic differences in the likelihood of aspiring to university? Third, how are parenting behaviours and closed parental networks at the individual and school cohort levels associated with ethnic differences in positive schoolwork attitudes and behaviours? Fourth, how are variations in the duration of residence in England and in additional language use, at the individual and school cohort levels, associated with ethnic differences in English language proficiency? English data from wave 1 of the Children of Immigrants Longitudinal Survey in Four European Countries (CILS4EU) and from the National Pupil Database (NPD) matched to the Pupil Level Annual School Census (PLASC) are used to answer these questions. Both datasets are used to analyse outcomes for a sample of the school cohort that turned 14 in the academic year 2009/10. The key findings are as follows. First, increases in school ethnic minority density are associated with increased progress; increases in school average poverty are associated with decreased progress. Second, individual level religiosity is positively associated with university aspirations, but cohort level religiosity has no association. Third, positive parenting behaviours are associated with improved schoolwork attitudes, whilst parental closure has positive effects at the individual level but not at the cohort level. Fourth, the duration of residence in England is a positive predictor of English language proficiency, whilst there is no effect of using an additional language. This thesis addresses a highly relevant social issue from a novel perspective, and has important implications for both policy and future research on this topic.